Do We Share a Book? The Sunday Lectionary and Jewish-Christian Relations - Peppard, Michael (Studies in Christian-Jewish Relations, 2011)
This paper analyzes the role that the Sunday Lectionary, revised after Vatican II, plays in the Catholic Church’s presentation of Jews and Judaism. The presentation of Jews and Judaism in the current Lectionary is clearly a vast improvement over what preceded it. However, there is still much work to be done in order to bring the Lectionary in line with official Catholic teachings on the Old Testament and the Jews. The recent document of the Pontifical Biblical Commission, The Jewish People and Their Sacred Scriptures in the Christian Bible (2001), provides a new and authoritative impetus to reconsider the selection of Old Testament texts and their relationship to Gospel texts in the Lectionary. The article argues that continued Lectionary reform â specifically with regard to the Old Testament lections â would improve Jewish-Christian relations in the long term.